Transboundary water projects by Turkey and Iran: The impacts on Iraqi water resources - Rashid, Hiwa; Abdul Rahim, Asmar (2020)
Over exploitation of lakes, rivers and aquifers will caused jeopardize these ecosystem services and have dire consequences for the reliability and sustainability of water supplies in some of the countries. The issue of the trans boundary water projects always cause tension between two countries when the project cause harm to the people of living to the effected country. Iraqi water resources for example has faced unprecedented stress and impact to environmental destruction caused by water projects carried out by Turkey and Iran on Ilisu and Daryan Dams’. These projects gave impact to Tigris, Euphrates and Shatt Al-Arab rivers in Iraq and violated Iraqi people the right to access equitable share of water. Thus, the objective of this paper is to analysis the legal responsibility of Turkey and Iran on their water projects and the impacts toward Iraqi water resources accordance to International laws perspective. The discussions of this paper adopt critical content analysis by using descriptive method. The paper found that the current development of water projects by Turkey and Iran have caused water shortage of Iraq water resources. The water projects carried out by Turkey and Iran also violated the principle right to access equitable share of water in accordance to international customary law, trans boundary water treaties and other related international principles.